Mechanics of epidermal morphogenesis in the Drosophila pupa. (December 2021) - Athilingam, Thamarailingam; Tiwari, Prabhat; Toyama, Yusuke; Saunders, Timothy E.
Abstract: Adult epidermal development in Drosophila showcases a striking balance between en masse spreading of the developing adult precursor tissues and retraction of the degenerating larval epidermis. The adult precursor tissues, driven by both intrinsic plasticity and extrinsic mechanical cues, shape the segments of the adult epidermis and appendages. Here, we review the tissue architectural changes that occur during epidermal morphogenesis in the Drosophila pupa, with a particular emphasis on the underlying mechanical principles. We highlight recent developments in our understanding of adult epidermal morphogenesis. We further discuss the forces that drive these morphogenetic events and finally outline open questions and challenges.